Special section: Process Integration, Modelling and Optimisation for Energy Saving and Pollution Reduction – PRES 2014. (October 2015) - Varbanov, Petar Sabev; Manenti, Flavio; Klemeš, Jiří Jaromír; Lund, Henrik
Abstract: This Special Issue contains a selected set of articles developed from initial ideas related to the 17th Conference Process Integration, Modelling and Optimisation for Energy Saving and Pollution Reduction (PRES'14) held in Prague, Czech Republic, during 23–27 August 2014 Prague, Czech Republic. The conference has been held jointly with CHISA 2014, where both events have benefitted from the shared pool of presenters, listeners as well as the expanded opportunities for exchanging ideas. From all contributions presented at the conference, a selection of high-quality ones suitable for ENERGY, have been invited. Overall, 41 extended manuscripts have been submitted as candidate articles for the Special Issue. Of those, after a thorough review procedure, 16 articles have been selected and evolved to be published. The topics clearly reflect the variety of the ideas and discussions, exchanged and taken place at PRES 2014. The system types and phenomena include heat exchange and recovery, power generation ànd use, Combined Heat and Power generation. The key issues concern waste heat recovery and valorisation, process improvement – including process intensification, load shifting, biomass and solar irradiation as energy sources, supply chains, emissions and CO2 capture, production planning.